Cosmopolitan dharma : race, sexuality, and gender in British Buddhism - Smith, Sharon E., 1962-2011. (Numen Book Series, 2016)
Within Western Buddhism, practitioners are often assumed to be white and middle-class. Based in ground-breaking empirical research, Cosmopolitan Dharma: Race, Sexuality, and Gender in British Buddhism explores the stories of Buddhists from minority communities, through a rich analysis of their lived experiences. Smith, Munt and Yip explore their various contestations of dominant white and heteronormative cultures in Western Buddhism. Using cosmopolitanism as the theoretical lens, Cosmopolitan Dharma argues convincingly that the Buddhist ethos of human interconnectivity needs to be further developed to truly embrace the 'Other' of different kinds (not least Western Buddhism's own internal 'Others'). Cosmopolitan Dharma , through Buddhists' own narratives, explores how cultural politics from the ground up can offer a more inclusive philosophy and lived experience of spirituality.